Abnormal Mitochondrial Quality Control in Neurodegenerative Diseases - Yan, Xu; Wang, Biyao; Hu, Yue; Wang, Sijian; Zhang, Xinwen (Frontiers in Cellular Neuroscience, 2020)
Neurodegenerative diseases, including Alzheimer’s, Parkinson’s, Huntington’s and Amyotrophic Lateral Sclerosis (ALS), are characterized by a progressive loss of selective neuron subtypes in the central nervous system (CNS). Although various factors account for the initiation and development of these diseases, accumulating evidence shows that impaired mitochondrial function is a prominent and common mechanism. Mitochondria play a critical role in neurons, and are involved in energy production, cellular metabolism regulation, intracellular calcium homeostasis, immune responses and cell fate. Thus, cells in the CNS heavily rely on mitochondrial integrity. Many aspects of mitochondrial dysfunction are manifested in neurodegenerative diseases, including aberrant mitochondrial quality control (mitoQC), mitochondrial-driven inflammation and bioenergetic defects. Herein, we briefly summarize the molecular basis of mitoQC, including mitochondrial proteostasis, biogenesis, dynamics and organelle degradation. We also focus on the research - to date - regarding aberrant mitoQC and mitochondrial-driven inflammation in several common neurodegenerative diseases. In addition, we outline novel therapeutic strategies that target aberrant mitoQC in neurodegenerative diseases.